IMPLEMENTASI TEKNOLOGI BIOGAS DARI KOTORAN SAPI SEBAGAI SOLUSI ENERGI TERBARUKAN DI DESA MUARA PENIMBUNG: IMPLEMENTATION OF AN INTEGRATED BIOGAS-BASED CATTLE MANURE MANAGEMENT TECHNOLOGY AS A RENEWABLE ENERGY SOLUTION IN MUARA PENIMBUNG VILLAGE - Harlin; Anugerah Agung Ramadhan; Yogi herdianto; Ainun Maulidina; Puteri Anggieta Cahyani; Efri Meldianto (LPPM Universitas Abdurrab, 2026)
This Community Service Program (PkM) was implemented in Muara Penimbung Village as an effort to address environmental pollution caused by cattle manure waste and the community’s high dependence on LPG and firewood. The program implemented a 1 m³ biogas digester technology as a renewable energy solution as well as an environmentally friendly waste management system. The implementation stages included a needs assessment survey of partners, program socialization, technical training on digester construction and operation, operational demonstrations, and continuous usage assistance. The results showed an increase in community knowledge and skills related to the anaerobic fermentation process, digester operation, and the utilization of slurry as organic fertilizer. Quantitatively, more than 80% of participants were able to operate the digester independently, and the installed system produced an average biogas output of 0.25-0.30 m³ per day, which was sufficient to meet the daily cooking needs of partner households. Furthermore, all cattle manure waste was processed more effectively, thereby reducing environmental pollution around the cattle sheds. This program had a positive impact on environmental, economic, and social aspects of the community and supported the achievement of the Sustainable Development Goals (SDGs), particularly clean and affordable energy, environmental health, and community capacity building. The success of this program provides a strong foundation for the future development and replication of biogas technology among other livestock farmers.